2015
DOI: 10.1111/jgh.12970
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of once a day rifaximin to twice a day dosage in the prevention of recurrence of hepatic encephalopathy in patients with chronic liver disease

Abstract: This study suggests that there is no significant difference in rifaximin once a day or twice daily dose in preventing HE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…Studies have also assessed the effectiveness of different rifaximin treatment regimens when used in addition to lactulose therapy. No significant differences were observed between patients treated with rifaximin-α 550 mg once-daily versus twice daily 25, or between patients treated with rifaximin-α 550 mg twice daily versus rifaximin 400 mg, three times daily; although rifaximin-α 550 mg twice daily was shown to be more cost-effective than the three times daily regimen 27.…”
Section: Resultsmentioning
confidence: 88%
“…Studies have also assessed the effectiveness of different rifaximin treatment regimens when used in addition to lactulose therapy. No significant differences were observed between patients treated with rifaximin-α 550 mg once-daily versus twice daily 25, or between patients treated with rifaximin-α 550 mg twice daily versus rifaximin 400 mg, three times daily; although rifaximin-α 550 mg twice daily was shown to be more cost-effective than the three times daily regimen 27.…”
Section: Resultsmentioning
confidence: 88%
“…Regarding the dosage of rifaximin, Khokhar et al found no significant difference in the efficacy of rifaximin (550 mg) once daily and twice daily (550 mg/day and 1,100 mg/ day, respectively) in the prevention of HE (29). In contrast, however, Sarwar et al reported that the rate of HE development during 6 months of follow-up was similar between a low-dose (400 mg/day) group and a full-dose group (1,100 mg/day) (30).…”
Section: Discussionmentioning
confidence: 99%
“…As with all medications, efforts to reduce cost are prudent to aid in optimized patient compliance. A recent study by Khokar and colleagues examined the potential utility of rifaximin dosed at 550 mg taken only once daily . When comparing this regimen to the standard 550 mg twice daily regimen, they found no significant difference in their outcome of breakthrough episode of encephalopathy .…”
Section: Discussionmentioning
confidence: 99%